(untitled) (Biological Sciences - PJSIR, 2007)
. A com parat ive st udy on th e effectiveness of l’ri sod i um ph osph ate (TSP), citric acid (CA ) and gamm a rad i ati on i n th e con trol of £. coli O 1 57:H 7, Salm.one/l a En teritidi s and Staphylococcus aureus in beef and ch icken meat was un dertaken . I n beef meat sampl es i nocul ated with E. coli O I 57:H7 and t reated with I 0% sol ution of commerci al grade CA , ex tra pure CA and TSP for I O m i n , th e bacteria l count was reduced 2.2, 2.3 and 4 .9 log, respectively . Si mil arl y when ch icken meat samples were i n ocul ated wi th S. Enteri tidis and treated l 0% sol uti on of extra pure CA and TSP for I O mi n, the i nitial count was reduced by 3.5 and 5.2 l og, respectively. In beef and chi cken meat samples, inocul ated with E. coli O I 57:H7, S. Enteritidis , and Staphylococcus aureus and subjected to gamma radiat i on s, an absorbed dose of 2 kGy was n eeded to elimi n ate th e £. coli 0 l 57:H 7. 3 kGy was adeq uate to eli min ate t h e S Enteritid i s, and 4 kGy was found adequate to elim i nate the S aureus.